Etiological factors of congenital hearing loss in children – A high risk registerbased study - Jijo P M; Vipin Ghosh P G; Prawin Kumar (Journal of All India Institute of Speech and Hearing, 2013)
The study aimed to investigate the possible etiological factors of congenital severe to profound sensorineural hearing loss in children. The study also analyzed any difference in etiology, as a factor of geographic locations, socio-economic status, religious-community and gender. A survey-based study was carried out at the Department of Audiology, AIISH. A high-risk register was administered on parents of 70 children with congenital severe to profound sensorineural hearing loss. It was found that 73% of the participants had at least one causative factor associated with their condition whereas the remaining 27% had idiopathic onset of hearing loss. Parental consanguinity (31%) was the most common cause followed by maternal infections (13%), history of high fever (7%), NICU care more than a week (6%), family history of congenital hearing loss (4%), neonatal hyperbilirubinemia (4%) delayed birth cry (4%) medications in the first trimester (3%). Additionally, the etiological factors were analyzed in terms of geographic locations, socio-economic status, religious community and gender. Results revealed a significant difference in occurrence of consanguinity between the two geographical locations, religious community and gender. It can be concluded that consanguineous marriage as a major etiological factor that lead to congenital severe to profound hearing loss should be discouraged. Preventive measures should focus on geographic locations, socio-economic status, and religious community that exhibit higher rate of consanguineous marriages. Public education should be carried out regarding the adverse effect of interrelated marriages. Genetic counseling has to be carried out at least for those at risk of developing genetic diseases, including hearing impairment. Premarital and antenatal screening can also to be utilized.